Observations Over a Century Underscore an Increasing Likelihood of Compound Dry‐Hot Events in China - Ruixin Duan; Guohe Huang; Feng Wang; Chuyin Tian; Xinying Wu (Earth's Future)
Abstract The impacts of extreme events are seldom caused by a single climatic variable but rather arise from the interaction of multiple climate drivers. This study employs observational data sets with high spatiotemporal resolution to analyze the risk of occurrence of compound dry‐hot events in China over the past 120 years (i.e., 1901–2020). Simultaneously, attribution analysis based on distribution functions explores whether and to what extent human activities influence the occurrence of compound events. The results indicate that over the historical 120‐year period, the frequency of compound dry‐hot events in China has gradually increased, with the highest frequency observed in the most recent 40 years (i.e., 1981–2020). The frequency of compound dry‐hot events during this period is approximately four times that of 1901–1940 and about twice that of 1941–1980. The analysis of the relative importance of different factors reveals that temperature changes contribute more (56%) to the occurrence of compound events than precipitation (23%), and also exceed the interaction between them (21%). The substantial increase in compound dry‐hot events is largely attributed to the influence of human activities. Across seven sub‐regions, human activities have led to an increase in the probability of compound events occurring, ranging from 7.9% to 31.6%. The findings of this study indicate that human activities have significant implications for explaining the observed increase in compound hot and dry events over the past 40 years.